SUPERVISION OF THE RENOVATION OF MUSHOLLA NURUL ISLAM IN KP. SITUPETE SUKADAMAI VILLAGE OF TANAH SAREAL DISTRICT OF BOGOR CITY - Abdul Mubarok; Edison Hatoguan Manurung; Alip Prajoko; Kasimir Sawito (Yayasan Education and Social Center, 2021)
As a manifestation of the elaboration of the Tri Dharma of University, Community Service Activities have been carried out in the Nurul Islam Mosque Development Implementation program, which is located in Kp. Situpete RT. 01/06 Kel. Sukadamai Kec Tanah Sareal Bogor City. The main objective of this activity is to assist residents in the construction of the Mushola in the form of technical consultation assistance during construction. As time goes by, many changes have occurred to the condition of the mosque, which is becoming more and more obsolete. Currently, there is physical damage to the mosque building due to age, and it needs to be renovated because in some parts, such as the roof damaged or decayed wood, the ceiling condition has been damaged a lot due to leaks by rainwater during congregational prayers and the arrival of the holy month of Ramadan for congregational tarawih prayers is worried that when it rains it can cause leaks. This condition causes the implementation of worship to be less solemn and uncomfortable. Conditions like this have led to the desire to renovate the facilities and infrastructure of the mosque so that it can carry out its function as a place of worship and a place for fostering the morals of the people. A representative mosque, directly or indirectly, will find it easier to carry out its functions. This condition has inspired the Nurul Islam Mosque congregation to provide a place of worship that is more comfortable and capable of guiding the people. In the Qur'an Karim, the letter At Taubah verse 18, ALLAH SWT says: